Temporal variability of bacterioplankton is habitat driven. Issue 21 (26th September 2018) - Obertegger, Ulrike; Bertilsson, Stefan; Pindo, Massimo; Larger, Simone; Flaim, Giovanna
Abstract: Temporal dynamics of bacterioplankton are rarely investigated for multiple habitats and years within individual lakes, limiting our understanding of the variability of bacterioplankton community (BC) composition with respect to environmental factors. We assessed the BC composition of a littoral and two pelagic habitats (euphotic zone and hypolimnion) of Lake Tovel monthly from April 2014 to May 2017 by high‐throughput sequencing of the V3–V4 hypervariable region of the 16S rRNA gene. The three habitats differed in temperature, light, oxygen and hydrology. In particular, the littoral was the most hydrologically unstable because it receives most of the lake inflow, the hypolimnion was the most stable because of its hydrologically sheltered position, and the pelagic euphotic habitat was intermediate. Consequently, we hypothesized different temporal patterns of BC composition for all three habitats according to their environmental differences. We applied PERMANOVA, nonmetric multidimensional scaling and source–sink analysis to characterize BC composition. Overall, BCs were different among habitats with the littoral showing the highest variability and the hypolimnion the highest stability. The BC of rainy 2014 was distinct from the BCs of other years irrespective of the habitats considered. Seasonal differences in BCs were limited to spring, probably linked to meltwater inflow and mixing. Thus, temporal effects related to year and season were linked to the hydrological gradient of habitats. We suggest that despite potential within‐lake dispersal of bacterioplankton by water flow and mixing, local environmental conditions played a major role in Lake Tovel, fostering distinct BCs in the three habitats.